GAMBARAN KEJADIAN BODY SHAMING DAN KONSEP DIRI PADA REMAJA DI SMKN 1 KUOK - Alini Alini; Langen Nidhana Meisyalla (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Adolescence is a period where there is a change or transition from children to adults that begins at the age of 12 years and will end in the early 20s. Physical condition can be one of the differentiator in teenagers. Physical conditions can make a teenager feel afraid in social relationships. The term body shaming is intended to mock those who have a physical appearance that is considered quite different from society in general.Body shaming is one type of bullying where the individual is seen as a negative side of his physical appearance by others. Body shaming can affect adolescent self-concept. Self-concept is the way an individual sees himself as a whole. In adolescence, self-concept is an important category to reveal about his identity. The purpose of the study was to find out the description of body shaming and self-concept in students at SMK Negeri 1 Kuok in 2021. The type of research was quantitative research with descriptive analysis design. The study was conducted on July 8, 2021 with a sample of 158 students at SMK Negeri 1 Kuok using a stratified random sampling technique. Data collection using an online questionnaire. Analysis of the data used is univariate analysis. The results of univariate analysis showed that 85 respondents (53.8%) experienced high body shaming and 89 respondents (56.6%) had low self-concept. Respondents are expected to be able to further improve their self-concept by starting to love themselves to stay happy, and for respondents who experience body shaming further increase their potential.